Tuning of the electronic structure and reactivity of metal complexes with redox-active guanidine ligands - Holzmann, Simone L.; Osterbrink, Johanna; Hübner, Olaf; Schulz, Maximilian; Poddel'sky, Andrey; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2025)
Redox-active ligands change more drastically the electronic structure of metal complexes than non-redox-active ligands, with consequences on the magnetic and optical properties as well as the (redox) reactivity. In this work, redox-active guanidine ligands are integrated in cobalt and copper complexes. The variations in the electronic structures of cobalt complexes, in particular the relative energies of the states corresponding to high-spin CoII or low-spin CoIII, in dependence of the redox-active o-diguanidine ligand manifest themselves in different magnetic properties. Moreover, the electron transfer rates for copper complexes with two redox-active diguanidino-benzene ligands (self-exchange betweeen a monocationic CuI complex and the corresponding dicationic complex) were varied systematically over two orders of magnitude by choice of the redox-active diguanidine ligand, realizing redox pairs with intermediate or record-high rates.
Zuerst veröffentlicht: 26. September 2024
Gesehen am 03.03.2025